Nature Embodied : Gesture in Ancient Rome - Corbeill, Anthony, 1960- (Book collections on Project MUSE., 2004)
"Bodily gesture. A Roman worshipper spins in a circle in front of a temple. Faced with death, a Roman woman tears her hair and beats her breasts. Enthusiastic spectators at a gladiatorial event gesticulate with thumbs. Examining the tantalizing glimpses of ancient bodies offered by surviving Roman sculptures, paintings, and literary texts, Anthony Corbeill analyzes the role of gesture in medical and religious ritual, in the gladiatorial arena, in mourning practice, in aristocratic competition of the late Republic, and in the court of the emperor Tiberius. Adopting approaches from anthropology, gender studies, and ecological theory, Nature Embodied offers both a series of case studies and an overarching narrative of the role and meanings of gesture in ancient Rome."--Jacket